2019
DOI: 10.1111/ene.13965
|View full text |Cite
|
Sign up to set email alerts
|

Neurofilament light chain levels in pregnant multiple sclerosis patients: a prospective cohort study

Abstract: Background and purpose Neurofilament light chain is a cytoskeletal protein of neurons. Its levels are increasingly recognized as measures of neuroaxonal damage. The aim of this study was to explore serum neurofilament light chain (sNfL) levels in multiple sclerosis (MS) patients and healthy controls during pregnancy and puerperium. Methods This was a prospective, longitudinal, single‐center study. sNfL concentration was assessed using a highly sensitive single‐molecule array during pregnancy and in puerperium,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…In initial studies of blood NfL using ECL technology showed an association between serum NfL and brain atrophy over 2 years and number of MRI lesions, 64 though it had a poor prognostic value for patients with clinically isolated syndrome later converting to MS. 65 These studies on a small group of patients were limited by the sensitivity of the assay. 11 The high sensitivity of the SIMOA â technology provided the reliable quantification of blood NfL in MS. 11 On the group level, blood NfL in MS was higher than in healthy controls 32,44,62,66 with progressive MS having higher levels of blood NfL than relapsing MS. 16,32 The increased levels of blood NfL in progressive versus relapsing MS was unexpected and contrasted with lower levels of NfL in the CSF in progressive versus relapsing MS. 67 This remains unexplained but could be related to a breakdown of the BBB in progressive MS linked to aging and/or a contribution from the peripheral nervous system. Ascherio's group reported that in a military cohort, blood NfL was able to identify neuronal damage 6 years prior to the clinical disease onset, 68 thus neurodegeneration was already present at the prodromal stage of MS. A number of studies have found that disease activity as measured by clinical or MRI assessment is associated with an increase in blood NfL levels in both adult 16,32,66,[69][70][71][72][73] and pediatric patients.…”
Section: Blood Nfl In Neurological Diseasesmentioning
confidence: 98%
See 4 more Smart Citations
“…In initial studies of blood NfL using ECL technology showed an association between serum NfL and brain atrophy over 2 years and number of MRI lesions, 64 though it had a poor prognostic value for patients with clinically isolated syndrome later converting to MS. 65 These studies on a small group of patients were limited by the sensitivity of the assay. 11 The high sensitivity of the SIMOA â technology provided the reliable quantification of blood NfL in MS. 11 On the group level, blood NfL in MS was higher than in healthy controls 32,44,62,66 with progressive MS having higher levels of blood NfL than relapsing MS. 16,32 The increased levels of blood NfL in progressive versus relapsing MS was unexpected and contrasted with lower levels of NfL in the CSF in progressive versus relapsing MS. 67 This remains unexplained but could be related to a breakdown of the BBB in progressive MS linked to aging and/or a contribution from the peripheral nervous system. Ascherio's group reported that in a military cohort, blood NfL was able to identify neuronal damage 6 years prior to the clinical disease onset, 68 thus neurodegeneration was already present at the prodromal stage of MS. A number of studies have found that disease activity as measured by clinical or MRI assessment is associated with an increase in blood NfL levels in both adult 16,32,66,[69][70][71][72][73] and pediatric patients.…”
Section: Blood Nfl In Neurological Diseasesmentioning
confidence: 98%
“…16,69,70 The known reduction in disease activity during pregnancy 77 was reflected by similar blood NfL levels among pregnant healthy women and MS patients. 62 It is not known whether this was related to the physiological increase in blood volume that occurs during pregnancy. 60 With a better understanding of the role of NfL and the development of sensitive and reproducible assays, a fertile ground has developed for the use of blood NfL in clinical studies.…”
Section: Blood Nfl In Neurological Diseasesmentioning
confidence: 99%
See 3 more Smart Citations